Numerical analysis of a spectral photoelastic effect - Gajewski, Tadeusz; Konwerska-Hrabowska, Joanna (Computer Assisted Methods in Engineering and Science, 2023)
Interference effects in centers of "disk-like" solid cylinders of different photoelastic materials loaded by uniaxial forces acting along diameters was subject of study. An analysis of the intensity of light passing through the cylinder was carried out, and a few numerical models of the phenomenon were constructed and compared with the experimental results. The dispersive character of the "photo elastic constant" is shown and its consequence for the effect are emphasized. A computer aided spectrometer was specially constructed for the research as "the heart" of a semi-automatic measurement stand. The utilization of the effect for the construction of the optical force sensor is mentioned.